Power and standardisation in doctoral education : a Gramscian perspective on South Africa’s NQF and CHE policies - Amin, Nyna; Aldous, Colleen; Devroop, Chatradari (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
In this article, the descriptors of the National Qualifications Framework (NQF) Level 10 and the Council on Higher Education (CHE) doctoral attributes in South Africa are critically explored using the concept of cultural hegemony by Antonio Gramsci. The study employs a comparative analytical approach to reveal the power and ideological dynamics of these frameworks as Gramsci understood culture as a practice, not as a value system. Document analysis and thematic comparison reveal how these standards reflect and may even challenge current structures of hegemony in doctoral education. The NQF Level 10 descriptors maintain standardisation based on traditional academic excellence concepts, while the CHE doctoral attributes redefine doctoral education to embrace social responsibility and contextual relevance. Gramsci’s educational theory requires us to consider both conformity and spontaneity when we analyse these frameworks. We argue that even though these frameworks are necessary to organise doctoral education in South Africa, they can become hegemonic and limit the organic and dynamic nature of cultural and pedagogical processes. Our proposal for a transformative strategy for doctoral education engages critically with these frameworks while allowing for spontaneous and other kinds of knowledge
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 8, Volume 9, 2025
Keywords: CHE doctoral attributes; Cultural hegemony; Doctoral education; NQF Level 10; Power dynamics; Doctoral students; Hegemony; Doctor of philosophy degree -- South Africa; Academic achievement -- South Africa; Education higher, South Africa